2005
DOI: 10.1007/s00535-005-1649-1
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection increases the risk of colorectal adenoma and adenocarcinoma, especially in women

Abstract: The results therefore suggest that, in patients aged 40-80 years, H. pylori infection increased the risk of colorectal adenoma and adenocarcinoma, with significantly higher risks for female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 36 publications
1
68
2
Order By: Relevance
“…A limited number of previous hospital-based case-control (22,23) and comparative studies (24)(25)(26)(27)(28) have reported an increased risk of colorectal neoplasia in the presence of H. pylori infection. As for CAG, two reports have described non-significant results for the correlation between colorectal cancer and CAG (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of previous hospital-based case-control (22,23) and comparative studies (24)(25)(26)(27)(28) have reported an increased risk of colorectal neoplasia in the presence of H. pylori infection. As for CAG, two reports have described non-significant results for the correlation between colorectal cancer and CAG (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the greatest risk for colonic adenomas in women is associated with hormonal factors (6) . The mean age of the female patients examined in this study was over 50 years, so they probably had reduced levels of sex hormones.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen and progesterone reduce the risk of adenomas and of adenocarcinomas in the colon. A possible interaction between H. pylori and low levels of female sex hormones was described in the development of colonic neoplasias in women (6) . When the cases in our study were evaluated in accordance with the histological type of the adenomas, the data showed that H. pylori infection was significantly prevalent only in individuals with tubular adenomas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that the frequent coexistence of colonic polyps and gastric IM may not be explained only by H. pylori infection and hypergastrinemic atrophic gastritis. A study by Fujimori et al (27) in Japan reported a steadily decreasing prevalence of H. pylori infection, while the prevalence of CRC increased. Other factors besides H. pylori infection might increase the rate of CRC; however, further investigations are required.…”
Section: Discussionmentioning
confidence: 99%